A cross-sectional study on chronic disease in the middle-aged after COVID-19 fortified edible cosmeceuticals for improving health functionality - Lee, Jinkyung; Kwon, Ki Han (Progress in Nutrition, 2024)
Introduction: This paper used big data based on the previous H1N1 influenza that was prevalent worldwide in 2012. Objectives: We are aiming to develop elderly-friendly functional foods according to the domestic influenza epidemic and to understand the importance of sustainable and healthy beauty. Using big data as a research method, prognostic evaluation of coronavirus infection-19 (COVID-19) was performed. Methods: Statistical data were collected from the 5th National Health and Nutrition Survey (KNHANES V-3, 2012) conducted by the Ministry of Health and Welfare of the Republic of Korea. Of the 7,214 survey respondents on the entire KNHANES V-3 Big Data, 3,150 participants belonged to the senior group aged 50-65 years or older. Results: The intake of health functional foods within one year of the elderly over 50 is as follows. Daily intakes of vitamin A, thiamine, riboflavin, and niacin were shown to be sufficient, and intake of vitamin C was significantly higher at 100–143% of the recommended intake. The foundation of this study was based on big data of the Korean population in Korea at the time of the H1N1 influenza epidemic. Conclusions: The results of this study are expected to help improve the diet of the senior population, the elderly, and develop customized edible cosmeceuticals through sustainable and safe dietary supplements in the context of the global pandemic COVID-19.